Impact of wormlike micelles on nano and macroscopic structure of TEMPO-oxidized cellulose nanofibril hydrogels. Issue 20 (19th May 2020) - da Silva, Marcelo A.; Calabrese, Vincenzo; Schmitt, Julien; Hossain, Kazi M. Zakir; Bryant, Saffron J.; Mahmoudi, Najet; Scott, Janet L.; Edler, Karen J.
Abstract : The shape of mixed surfactant micelles alters the rheological properties of TEMPO-oxidized cellulose nanofibril (OCNF) saline dispersions. Abstract : In this work, we investigated the effect of adding surfactant mixtures on the rheological properties of TEMPO-oxidized cellulose nanofibril (OCNF) saline dispersions. Three surfactant mixtures were studied: cocamidopropyl betaine (CAPB)/sodium dodecyl sulfate (SDS), which forms wormlike micelles (WLMs); cocamidopropylamine oxide (CAPOx)/SDS, which forms long rods; and CAPB/sodium lauroyl sarcosinate (SLS), which forms spherical micelles. The presence of micelles in these surfactant mixtures, independent of their morphology, leads to an increase of tan  δ, making the gels less solid-like, therefore acting as a plasticizer. WLMs were able to suppress strain stiffening normally observed in OCNF gels at large strains. OCNF/WLM gels have lower G ′ values than OCNF gels while the other micellar morphologies have a reduced impact on G ′. The presence of unconnected micelles leads to increased dissipative deformation in OCNF gels without affecting the connectivity of the fibrils, while the presence of entangled micelles interferes with the OCNF network.